Additively manufactured oxide dispersion strengthened nickel-based superalloy with superior high temperature properties. (8th December 2020) - Tan, Liming; Wang, Guowei; Guo, Yu; Fang, Qihong; Liu, Zecheng; Xiao, Xiangyou; He, Wuqiang; Qin, Zijun; Zhang, Yong; Liu, Feng; Huang, Lan
ABSTRACT: With excellent radiation resistance and high temperature strength, the oxide dispersion strengthened (ODS) nickel-based superalloys are deemed as candidate materials for advanced fission and fusion reactor. Since conventional manufacturing processes are difficult to produce components with complex shapes, additive manufacturing becomes an alternative method. In this work, ODS nickel-based superalloy was manufactured by laser metal deposition (LMD) technology using mechanically alloyed powder. The microstructure and high temperature mechanical properties of the as-deposited alloy were analysed. The results indicated that the as-deposited alloys prepared by this method owned anisotropic structure and uniformly distributed high-density oxides, contributing to superior high-temperature performance, in comparison with the samples produced by LMD using pre-alloyed powder and traditional hot extrusion.